Comparison of different neoadjuvant treatments for resectable locoregional esophageal cancer: A systematic review and network meta‐analysis. Issue 17 (26th July 2022) - Bao, Yongxing; Ma, Zeliang; Yuan, Meng; Wang, Yang; Men, Yu; Hui, Zhouguang
Abstract: Purpose: The best pattern of neoadjuvant therapy for resectable locoregional esophageal cancer has not been determined. Our study evaluated the efficacy and postoperative events of different treatments using the Bayesian network meta‐analysis. Methods: We systematically tracked randomized clinical trials from the Medline, EMBASE, and Cochrane Library databases. The following treatments were included: neoadjuvant chemoradiation followed by surgery (NCRT + S), neoadjuvant chemotherapy followed by surgery (NCT + S), neoadjuvant radiotherapy followed by surgery (NRT + S), and surgery alone (S). The Revised Cochrane risk‐of‐bias tools were used to assess the quality of included trials. Overall survival (OS) and progression‐free survival or disease‐free survival (PFS/DFS) were assessed through hazard ratios (HR). Locoregional recurrence, distant metastasis, postoperative mortality, and postoperative morbidity were assessed through odds ratios (OR). These outcomes were compared between different treatments through Bayesian network meta‐analysis. Results: Twenty trials with 4384 patients were included. Compared with S, only NCRT + S could significantly improve OS for patients with esophageal cancer (HR = 0.78, 95% confidence interval [CI] 0.68–0.88). NCRT + S and NCT + S significantly improved PFS/DFS compared with S (NCRT + S vs. S, HR = 0.72, 95% CI 0.63–0.81; NCT + S vs. S, HR = 0.81, 95% CI 0.69–0.97). NCRT + S significantly reduced both locoregional recurrence (OR = 0.67, 95% CI 0.51–0.88) and distant metastasis (OR = 0.63, 95% CI 0.45–0.90) compared with S. There were no differences in postoperative morbidity between the four treatments. However, NCRT + S also increased postoperative mortality compared with S (OR = 1.77, 95% CI 1.09–2.82) and NCT + S (OR = 1.96, 95% CI 1.11–3.51). Conclusion: NCRT + S is the most efficient neoadjuvant treatment for resectable locoregional esophageal cancer. However, NCRT + S increases the risk of postoperative mortality but not morbidity. Abstract : Our study evaluated the efficacy and postoperative events of different treatments by using the Bayesian net‐work meta‐analysis. Randomized clinical trials from Medline, EMBASE, and Cochrane Library database were systematically tracked. The following treatments were included: neoadjuvant chemoradiation followed by surgery (NCRT+S), neoadjuvant chemotherapy followed by surgery (NCT+S), neoadjuvant radiotherapy followed by surgery (NRT+S), and surgery alone (S). Twenty trials with 4384 patients were included. Compared with S, only NCRT+S could significantly improve OS for patients with esophageal cancer (HR=0.78, 95% CI: 0.68‐0.88). NCRT+S and NCT+S significantly improved PFS/DFS compared with S (NCRT+S vs. S, HR=0.72, 95% CI: 0.63‐0.81; NCT+S vs. S, HR=0.81, 95%CI: 0.69‐0.97). NCRT+S significantly reduced both locoregional recurrence (OR=0.67, 95%CI: 0.51‐0.88) and distant metastasis (OR=0.63, 95%CI: 0.45‐0.90) compared with S. There were no differences in postoperative morbidity between the four treatments. However, NCRT+S also increased postoperative mortality compared with S (OR=1.77, 95%CI: 1.09‐2.82) and NCT+S (OR=1.96, 95%CI: 1.11‐3.51).